CRIXUS-TRUCOV: uma ferramenta para apoiar o teste estrutural de sistemas embarcados críticos - Bartko, William (2012)
Safety-critical systems are programmable devices designed to be functional, even when failures can produce catastrophic results.Its is necessary attention during the development of this systems in ordem to avoid this situations. However, te lake of specific tools to suport appropriated testing criteria and to support testing coverage of safety critical embedded systems results in error-prone software. In this work we propose a coverage testing tool to support the test of microcontroller systems implemented to PIC microcontrollers of microchip. The main objective of our tool is to aid testing activities during the development process of safety critical embedded software.